Preparation of local culture media for growth of Salmonella typhi - Bushra Daley Hamd; Mohsen Auob Essa (College of Education for Pure Sciences, 2009)
Abstract This study deals with the ability of preparing local culture Media which can be used as a suitable replacement of Blood agar medium used for diagnosis of Salmonella typhi by using some of plant and animals extracts as fish, dates and Alfalfa extracts. fish and dates extracts were used together to prepare a local medium, the study showed that the optimum proportions were (70)% fish extracts and (30)% dates extracts and other medium consists of fish and alfalfa extracts with an optimum proportions of (70)% fish extracts and (30)% alfalfa extracts, it selective and differential media were prepared and used to isolate and identify Salmonella typhi.